The Aesthetic of Decorative Composition in the Baghdad Mashrabiya (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
This paper will dwell on the aesthetical structure of the decorative elements of mashrabiya (shanasheel), a common architectural design of an Iraqi urban tradition. The study emphasizes the mashrabiya as a form of cultural identity that incorporates functional, environmental, and aesthetic values that lie within the context of history and civilisation. The study attempts to determine the visual, structural and decorative features that make the mashrabiya a unique artistic composition in Baghdad through the examination of selected samples of heritage neighborhoods on either sides of Baghdad (Karkh and Rusafa). The study takes the descriptive-analytical approach that is backed by field observation and record keeping, and it involves the correlation between the motives of geometry, vegetable, animal and abstract during the construction of decorative units. The results show that these units possess aesthetic values relating to harmony and balance, rhythm and unity as they replicate the intellectual and cultural aspects of the community creating such units. Moreover, the research concludes that Baghdad mashrabiya is a crucial part of maintaining the heritage identity and the urban memory, as well as providing the possibilities of the modern artistic and architectural innovation. It is suggested in the study that to maintain the aesthetic and cultural value of the mashrabiya art in modern architectural settings, more awareness, documentation, restoration and revival of mashrabiya art should be done.